MM-DTI: Visualization and segmentation tool for diffusion tensor images - Lobo, Renan R.S.; Rittner, Leticia; Lotufo, Roberto A.; Magalhães, Léo P. (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2010: Anais do X Workshop de Informática Médica, 2010)
In this paper we present the MM-DTI, a tool that offers diffusion tensor processing functionalities based on mathematical morphology operators. Through a graphic user interface, it is possible to configure and visualize a diffusion tensor image, to compute its tensorial morphological gradient (TMG) and finally, to segment it using the watershed transform. It offers three different visualization modes (tensor glyphs, volume rendering and tracts), three color mappings (FA-based, TMG-based and Segmentation-based) and an extra feature which provides an animation of the movement of water molecules through the interpolation of the objects position on the grid in the orientation and direction of the tensors principal eigenvector.